Survey Department in the Forum of International Activities: A Brief Overview - Sharma, Rabin Kaji (Journal on Geoinformatics, Nepal, 2004)
The scope of work of the Survey Department, Nepal is also related to Agenda 21 of Rio de Janeiro Earth Summit. In order to support this Agenda, the Department has joined the number of International Organizations as a member and participated in the forum of the activities organized by these organizations. Besides, the department has participated in the activities organized by some of the other institutions in which it is not a member. Therefore, the aim of this paper is to provide some views on the membership details and related activities of those organizations with which Survey Department, Nepal is actively involved. The role of the department in the forum has also been discussed.